Nuclear magnetic resonance study of ice-based composite materials reinforced with nanodisperse aluminum oxide fibers - Morozov, Evgeny V.; Voronin, A. S.; Kniga, S. V.; Buznik, Vyacheslav M. (Inorganic materials: applied research)
Pulsed-field gradient NMR spectroscopy and magnetic resonance imaging methods were used to investigate water suspensions of nanosized fibers of aluminum oxide and ice composite materials based on these fibers. Introduction of the nanofibers was shown to have no noticeable structural effect in the suspensions in the Al2O3 concentration range of 1-10 wt %. High content of the filler was found to change the morphology and texture of the ice matrix in the composites remarkably: it becomes more homogeneous and acquires a higher degree of continuity; the melting front does not visualize internal melting zones or integrity defects in the composite. At the same time, addition of the nanofibers to the ice composites weakly influences the quantitative dynamics of the heat transfer, which is manifested in close values of the propagation speeds of the freezing/melting front in the samples at similar temperatures.